The antimicrobial effects of Citrus limonum and Citrus aurantium essential oils on multi-species biofilms - Oliveira, Sarah Almeida Coelho; Zambrana, Jéssica Rabelo Mina; Di Iorio, Fernanda Bispo Reis; Pereira, Cristiane Aparecida; Jorge, Antonio Olavo Cardoso [UNESP] (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2014)
The aim of this study was to evaluate the effects of Citrus limonum and Citrus aurantium essential oils (EOs) compared to 0.2% chlorhexidine (CHX) and 1% sodium hypochlorite (NaOCl) on multi-species biofilms formed by Candida albicans, Enterococcus faecalis and Escherichia coli. The biofilms were grown in acrylic disks immersed in broth, inoculated with microbial suspension (106 cells/mL) and incubated at 37°C / 48 h. After the biofilms were formed, they were exposed for 5 minutes to the solutions (n = 10): C. aurantium EO, C. limonum EO, 0.2% CHX, 1% NaOCl or sterile saline solution [0.9% sodium chloride (NaCl)]. Next, the discs were placed in sterile 0.9% NaCl and sonicated to disperse the biofilms. Tenfold serial dilutions were performed and the aliquots were seeded onto selective agar and incubated at 37°C / 48 h. Next, the number of colony-forming units per milliliter was counted and analyzed statistically (Tukey test, p ≤ 0.05). C. aurantium EO and NaOCl inhibited the growth of all microorganisms in multi-species biofilms. C. limonum EO promoted a 100% reduction of C. albicans and E. coli, and 49.3% of E. faecalis. CHX was less effective against C. albicans and E. coli, yielding a reduction of 68.8% and 86.7%, respectively. However, the reduction of E. faecalis using CHX (81.7%) was greater than that obtained using C. limonum EO. Both Citrus limonum and Citrus aurantium EOs are effective in controlling multi-species biofilms; the microbial reductions achieved by EOs were not only similar to those of NaOCl, but even higher than those achieved by CHX, in some cases.
Keywords: Biofilms; Citrus limonum; Citrus aurantium